Comparison temperature distribution between microwave and radio-frequency ablation probe in hepatic cancer - Chaichanyut, M.; Tungjitkusolmun, S.; Potejanasaja, I.; Lertprasert, P. (My University, 2007)
This paper presents three-dimensional finite element analyses of hepatic cancer ablation. The analyses performed in this paper are composed of two systems. In the first system, the simulation was microwave ablation by using open-tip monopole antenna. We analyses microwave ablation at frequency of 2.45GHz. Additional simulations of radiofrequency ablation by using monopolar probe. All simulations, we studied and compared the characteristics of the electric field and temperature distributions between monopole antenna and monopolar probe. From the simulation results, the electric field distribution of open-tip monopole was a wide electric field distribution while the electric field distribution of monopolar has a narrower. The temperature distribution has distributed same with electric field distribution. The temperature distribution of open-tip monopole was larger when compared with monopolar probe.
Keywords: Electric field; Microwave ablation; Radio-frequency ablation